2016
DOI: 10.1093/mnras/stw166
|View full text |Cite
|
Sign up to set email alerts
|

The central parsecs of M87: jet emission and an elusive accretion disc

Abstract: We present the first simultaneous spectral energy distribution (SED) of M87 core at a scale of 0.4 arcsec (∼ 32 pc) across the electromagnetic spectrum. Two separate, quiescent, and active states are sampled that are characterized by a similar featureless SED of power-law form, and that are thus remarkably different from that of a canonical active galactic nuclei (AGN) or a radiatively inefficient accretion source. We show that the emission from a jet gives an excellent representation of the core of M87 core c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
154
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 144 publications
(168 citation statements)
references
References 95 publications
(136 reference statements)
12
154
0
Order By: Relevance
“…This same broadband SED was also used by Broderick et al (2015) to place similar constraints on the accretion rate and on the presence of an event horizon. Prieto et al (2016) also derive a similarly low accretion rate from the previous HST imaging data on the Hα emission line in the ionized gas disk discovered by Ford et al (1994). The absence of significant Faraday rotation for the M 87 nuclear source at sub-mm wavelengths is also consistent with a very low accretion rate (Kuo et al 2014).…”
Section: Introduction Low Powersupporting
confidence: 71%
See 1 more Smart Citation
“…This same broadband SED was also used by Broderick et al (2015) to place similar constraints on the accretion rate and on the presence of an event horizon. Prieto et al (2016) also derive a similarly low accretion rate from the previous HST imaging data on the Hα emission line in the ionized gas disk discovered by Ford et al (1994). The absence of significant Faraday rotation for the M 87 nuclear source at sub-mm wavelengths is also consistent with a very low accretion rate (Kuo et al 2014).…”
Section: Introduction Low Powersupporting
confidence: 71%
“…Detailed fitting of the spectral energy distribution (SED) within ∼ 30 pc of the nucleus of M87 by Prieto et al (2016) finds an SED dominated by jet emission throughout the electromagnetic spectrum excepting a small contribution from a cool accretion disk longward of 1µm. This corroborates earlier work by Perlman et al (2001Perlman et al ( , 2007.…”
Section: Introduction Low Powermentioning
confidence: 99%
“…For M87 whose bolometric luminosity is ∼10 −6 times smaller than the Eddington luminosity (L edd ) [21], Asada and Nakamura [2] suggest that the jet may be confined by a radiatively inefficient hot accretion flow (RIAF) with a geometrically-thick quasi-spherical shape (e.g., [22]). Indeed, recent 86 GHz observations of M87 have shown that the jet pressure at the 86 GHz core is comparable to the RIAF pressure, indicating that the pressure support from the hot accretion flow may be capable of shaping the M87 jet [5].…”
Section: Resultsmentioning
confidence: 99%
“…Schartmann et al 2014). Low Eddington sources are often powerful radio sources, best prototype is M87 (Prieto et al 2016, and references therein), and thus a jet in NGC 1386 is a plausible cause of the outflowing shells. NGC 1386 shows extended radio emission at each side of the nucleus along the N-S direction, the Southern emission being better defined and detached-from-the-core while the northern one appears as a protuberance.…”
Section: Discussionmentioning
confidence: 99%